Integrating Hasta Brata Values into Civil Service Leadership - Veronika Agustini Srimulyani; Yustinus Budi Hermanto (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2026)
This study aims to reactualize the values of Hasta Brata leadership within the context of Indonesia’s civil service resource management transformation. The research is motivated by the dominance of Western leadership theories in the bureaucracy, which often lack roots in Nusantara's cultural values, necessitating an indigenous leadership approach to strengthen the integrity and performance of the State Civil Apparatus (ASN). The method employed is qualitative, using a structured library research approach that systematically synthesizes recent academic literature, public-sector regulations, and the philosophy of the eight natural characters. The findings conceptually indicate that the eight natural characters of Hasta Brata—Earth (Kisma), Sun (Surya), Water/Ocean (Tirta/Banyu), Fire (Agni), Wind (Maruta), Moon (Candra), Stars (Kartika), and Sky (Akasa)—offer a novel framework with strong relevance to the ASN BerAKHLAK core values. This philosophy provides a holistic ethical foundation for building inclusive, accountable, and adaptive public services. As a conceptual study, the findings suggest that integrating Hasta Brata into the ASN leadership competency development curriculum could serve as an effective cultural transformation strategy, though future empirical validation is required. As a policy recommendation, this study proposes that the Hasta Brata indicator be integrated into the Assessment Center instrument for promotions to Senior Leadership Positions (JPT). The study's contribution is to provide a theoretical foundation that combines local philosophy with a modern meritocratic system.